Hubungan antara tingkat konsumsi coklat dan frekuensi makan kariogenik dengan kejadian karies gigi pada anak - Herdiyanah, Nining (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2024)
IntroductionDental caries is one of the most common oral health problems among children, primarily resulting from dietary patterns that include frequent consumption of sugary foods high in glucose and sucrose. Chocolate and other cariogenic foods are considered major risk factors that warrant attention. This study aims to investigate the relationship between the level of chocolate consumption and the frequency of cariogenic food intake with the incidence of dental caries among children at Al-Ikhlas Kindergarten in Kedung Dalem Village, Mauk District, Tangerang Regency, Banten. MethodsThis study employed a quantitative approach with a cross-sectional design. The sample consisted of 50 children selected through total sampling. Data were collected using questionnaires administered through interviews with both parents and children. The data were then analyzed using the Chi-square test to determine the relationship between the variables. ResultsThe findings revealed no statistically significant relationship between the level of chocolate consumption and the incidence of dental caries (p = 0.851). Although a considerable number of children who frequently consumed chocolate experienced moderate caries, the distribution was not statistically meaningful. In contrast, a highly significant relationship was found between the frequency of cariogenic food consumption and the incidence of dental caries (p = 0.000). Children with high-frequency consumption of cariogenic foods were more likely to experience moderate caries, while those with low-frequency consumption mostly did not develop caries. Conclusion and RecommendationsThe frequency of cariogenic food consumption significantly influences the incidence of dental caries in children, whereas chocolate consumption alone does not show a meaningful effect. These findings are expected to serve as a reference for parents in managing children's dietary habits to prevent early onset of dental caries.